Building Digital Pedagogical Expertise in Online and Flipped Learning: Insights from a Visiting Scholar Experience - Effendi Limbong; Ita Irawati; Ben Wadham; Safrul Muluk; Suryanto Suryanto; Muhammad Efflin Rizqallah Limbong (Jurnal Ilmiah Peuradeun, 2026)
The increasing adoption of online and flipped learning in higher education has focused primarily on student outcomes, leaving limited understanding of how educators develop digital pedagogical expertise through direct engagement with these instructional models. This study examined how a visiting scholar engaged in online and flipped learning practices, the dimensions of digital pedagogical expertise that emerged, and the contextual factors shaping this development. Using a qualitative phenomenological design, the study explored the experiences of a visiting lecturer at an Australian public university over one academic semester, complemented by learner perspectives from a postgraduate student. Data were collected through artifact analysis, non-participant observations, reflective journals, and semi-structured interviews, and analyzed using thematic analysis. The findings revealed that professional learning occurred through guided participation in integrated online–flipped instructional ecosystems, leading to the development of key competencies, including instructional transparency, guided autonomy, and multimodal feedback practices. The study also highlighted the significant role of institutional infrastructure, cultural expectations, and learning environments in mediating this process. This study concluded that digital pedagogical expertise was developed through structured experiential participation within authentic teaching contexts, rather than through technical training alone, offering important implications for faculty development and the design of digital pedagogy in higher education.